THE INFLUENCE OF ACADEMIC SUPERVISION, WORK ENVIRONMENT, AND WORK MOTIVATION ON TEACHER PERFORMANCE - Satria, Febri; Marwan, Marwan; Bahri, Saiful (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
This study aims to explore the influence of academic supervision, work environment, and work motivation on teacher performance at SDN Gugus 1 in Meureubo District, West Aceh. Specifically, the objectives are (1) to assess the impact of academic supervision on teacher performance, (2) to evaluate the influence of work environment on teacher performance, (3) to determine the effect of work motivation on teacher performance, and (4) to analyze the combined effect of academic supervision, work environment, and work motivation on teacher performance. The study employs a quantitative approach, targeting a population of 114 teachers, with a sample of 89 selected through proportional random sampling using the Slovin formula at a 5% error margin. Data were collected using a Likert-scale questionnaire, which underwent validity and reliability testing. Multiple linear regression analysis was employed for data analysis, along with hypothesis testing through t-tests and F-tests and the determination coefficient, all processed using SPSS 21. The results indicate that academic supervision significantly influences teacher performance, with a p-value of 0.003. Similarly, work motivation significantly impacts teacher performance with a p-value of 0.000, and the work environment also shows a significant positive influence with a p-value of 0.041. Furthermore, the simultaneous analysis reveals a significant combined effect of academic supervision, work environment, and work motivation on teacher performance, with a p-value of 0.000. These findings suggest that enhancing academic supervision, improving the work environment, and fostering teacher motivation can effectively boost teacher performance in SDN Gugus 1. The study's implications extend beyond the local context, offering practical recommendations for educational institutions aiming to improve teacher performance through strategic interventions in supervision, environment, and motivation.